Privacy Concerns and Information Sharing: The Perspective of the U-Shaped Curve - Hsu, Chien-Lung; Liao, Yi-Chuan; Lee, Ching-Wen; Chan, Lin Kun (Frontiers in Psychology, 2022)
Privacy concerns are a key predictor of information sharing, yet some critical issues remain unclear. Based on social capital theory, this study argues that the relationship between privacy concerns and information sharing is a U-shaped curve. Users with privacy concerns would not share their private information; however, such users would eventually share their information as long as they trust the website and its members. Furthermore, this study provides a contingency perspective, suggesting that the curvilinear relationship between privacy concerns and information sharing varies with the system evaluation perception and personal motivation levels. The results show that at a high level of system evaluation, the relationship between privacy concerns squared and information sharing is non-significant. In contrast, at a low level of system evaluation, there is a U-shaped relationship between privacy concerns and information sharing. Regarding motivation, the results were congruent with our expectations.